2020
DOI: 10.1002/ccr3.3255
|View full text |Cite
|
Sign up to set email alerts
|

Rosai Dorfman Disease —A rare case of cervical lymphadenopathy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The typical symptoms include painless enlarged bilateral cervical lymph nodes with fever, neutrophil elevation, elevated erythrocyte sedimentation rate, hyperglobulinemia, and other clinical symptoms [10]. However, our patient did not exhibit any symptoms, and the lesion was detected on a chest CT scan performed during a routine health checkup.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The typical symptoms include painless enlarged bilateral cervical lymph nodes with fever, neutrophil elevation, elevated erythrocyte sedimentation rate, hyperglobulinemia, and other clinical symptoms [10]. However, our patient did not exhibit any symptoms, and the lesion was detected on a chest CT scan performed during a routine health checkup.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have suggested that immunological dysregulation or infections with human herpes virus (HHV)-6, HHV-8, parvovirus B19, and Klebsiella are suspected causes. However, the evidence remains inconclusive [10].…”
Section: Discussionmentioning
confidence: 99%
“…The histiocytes will be positive for immunohistochemical stains S100 and part of CD68 and are typically negative for CD1a. Laboratory ndings in RDD include leukocytosis, neutrophilia, normocytic anemia, thrombocytosis, an elevated C-RP, ESR, ferritin levels and hypergammaglobulinemia [12]. However, these lab ndings are unspeci c.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest it is thought to be due to immune dysregulation or infections like HHV-6, HHV-8, parvovirus B19 and klebsiella. However, the evidence is inconclusive [ 8 ]. It also remained controversial about the association of IgG4 with RDD.…”
Section: Discussionmentioning
confidence: 99%
“…Though the clinical presentation of RDD is variable, the most common place is painless bilateral cervical lymphadenopathy [ 8 ]. It usually accompanied with other systemic symptoms such as fever, malaise, night sweats, or weight loss in the short term.…”
Section: Discussionmentioning
confidence: 99%